Impact of NSA-PRISM to National Information Security Strategy & Policy - Khudayer, Aiesha Y.; Abdulsalam, Rasha M.; Alshaibani, Suha M.; Ibrahim, Jamaludin (IRPN Publishers, 2014)
Due to the higher concern of information security and daily threats which could make a tremendous impact on businesses and consumers this paper will discuss information security surveillance programs called PRISM, which affects the national information security. Detailed information will be provided about the program and different perspectives of security practitioners and company owners as well as the explanation of the slides leaked by Edward Snowden NSA contractor. The paper will also discuss the security influences in terms of privacy, trust and security awareness.